Dynamic change of IDO1 activity predicts survival in patients with unresectable stage III NSCLC and chemoradiotherapy - Wu, Linfang; Wang, Daquan; Chen, Yanhua; Qian, Mingmin; Xu, Xin; Zhang, Tao; Bi, Nan; Wang, Luhua (Frontiers in Immunology, 2022)
Objective High activity of Indoleamine 2,3-dioxygenase1 (IDO1) in lung cancer patients converts tryptophan (Trp), which is the essential amino acid for T-cell metabolism, to kynurenine (Kyn) and consequently suppresses anti-tumor immune responses. We aimed to track the dynamics of IDO1 activity in stage III non-small cell lung cancer (NSCLC) patients who received first-line radiotherapy (RT) and explore its association with survival outcomes. Materials and methods Systemic IDO1 activity was calculated by Kyn : Trp ratio. Plasma levels of Kyn and Trp in 113 thoracic RT-received stage III NSCLC patients were measured by high-performance liquid chromatography before the initiation of RT. The dynamic change of IDO1 activity was followed in 24 patients by measuring the Kyn : Trp ratio before, during, and after RT administration. Results In 24 patients with dynamic tracking of plasma IDO1 activity, there were no significant alterations observed among the three time points (Friedman test, p = 0.13). The changing pattern of the Kyn : Trp ratio was divided into four groups: decreased consistently during RT, first increased, then decreased, increased consistently, first decreased then increased. Patients whose Kyn : Trp ratio kept decreasing or first increased then decreased were defined as the good-change group. The good-change status was identified as an independent positive factor for overall survival (OS) and progression-free survival (PFS) (p = 0.04; p = 0.01) in multivariate analysis among evaluated parameters. Patients with good change showed significantly superior local control than the bad-change group (p = 0.01, HR = 0.22). In 113 stage III NSCLC patients with pre-radiation Kyn : Trp ratio, a trend that high baseline IDO1 activity was associated with short OS was observed (p = 0.079). Conclusion Favorable change in IDO1 activity during RT was associated with superior OS, PFS, and local control. IDO1 activity is a promising biomarker for prognosis in stage III NSCLC patients.